Song of the lion [compact disc, unabridged] - Hillerman, Anne, 1949- (Hillerman, Tony, Leaphorn and Chee novel., 2017)
A deadly bombing takes Navajo Tribal cops Bernadette Manuelito, Jim Chee, and their mentor, the legendary Lieutenant Joe Leaphorn, back into the past to find a vengeful killer in this riveting Southwestern mystery from the best selling author of Spider Woman's Daughter and Rock with Wings.